Electoral Management in the Western Balkans – Overview of Institutional Setting - Marko Milenković (Srpska Politička Misao)
Countries of the Western Balkans (WB) – former federal units of Socialist Federal Republic of Yugoslavia and Albania have undergone a lengthy and complex process of democratisation from late 1980s. Free and fair elections are among the cornerstones of democratic consolidation. Even though the institutional setting for electoral management differs greatly across the globe, during the Europeanisation process it was widely recommended to transitional societies to set up independent electoral management bodies in other to guarantee fair electoral conditions, with standards mostly promoted by the Venice Commission of the Council of Europe (VC) and International Institute for Democracy and Electoral Assistance (IDEA). Based on this influence, all the countries of the WB have established electoral commissions that are to great extent formally independent from the executive, with the intention of being less prone to electoral meddling. This is enhanced by regular election monitoring in the region by the Organisation for Security and Cooperation in Europe (OSCE) and the process being followed and evaluated by both the European Union institutions and member states as part of fulfilment of the Copenhagen criteria to join the EU. This paper gives an overview of the institutional setting of electoral management in the WB that was created following the model of independent bodies and outlines main features of their design.